Kings, spirits and memory in central India - Deo, Aditya Pratap, author.
1 online resource
Keywords: "Part anthropological history and part memoir, this book is a unique study of the polity of the colonial-princely state of Kanker in central India. The author, a scion of the erstwhile ruling family of Kanker, delves into the oral accounts given in the ancestral deity practices of the mixed tribe-caste communities of the region to highlight popular narratives of its historical polity. As he struggles with his own dilemmas as ethnographer-king, what comes into view is a polity where the princely state is drawn out amidst a terrain of gods and spirits as much as that of law courts and magistrates, and political power is divided, contested and shared between the raja/state and the people. This study constitutes not only an intervention in the larger debate on the relationship between state formations and tribal peoples, but also on the very nature of history as a knowledge practice, especially the understandings of power, authority and sovereignty in it. Combining intensive ethnography, complementary archival work and crucial theoretical questions engaging social scientists worldwide, the author charts an unusual explanatory path that can allow us to meaningfully understand societies/peoples that have historically been marginalized and seen as different. This book will be of interest to students and researchers of history, anthropology, politics, religion, tribal society and Modern South Asia"--